Contested city : municipal politics and the rise of Nazism in Altona, 1917 - 1937 - McElligott, Anthony 1955- (Social history, popular culture, and politics in Germany, 1998)
List of illustrations -- List of tables -- Acknowledgments -- Map of Altona and North Germany -- Introduction -- "Rowdies" in Altona's Rathaus: politics and conflicts, 1917-1933 -- Clash of cultures: slum life and welfare, 1918-1932 -- "Save us from Altona!": the battle against incorporation, 1924-1927 -- Economic struggles: the local state and business interests, 1924-1932 -- Street politics in the crisis, 1930-1933 -- "Under the sign of the swastika!" The divided Volksgemeinschaft, 1933-1937 -- Conclusion: local state, central state, and contested state -- Epilogue: Brauer's return